An NFATC4 phospho-switch links matrix stiffness to fibroblast fate - Rebecca Shelley Frabotta; Purushothama Rao Tata (Journal of Clinical Investigation, 2026)
Fibrosis is driven by the activation of quiescent fibroblasts into contractile, matrix-secreting myofibroblasts, a transition governed jointly by biochemical signals and by the mechanical properties of the ECM. How the physical stiffness of tissue is converted into a durable transcriptional cell fate decision has remained poorly understood. In this issue of the JCI , Kadri et al. used global phosphoproteomic profiling of primary human lung fibroblasts across a defined stiffness gradient to identify phosphorylation of NFATC4 at residues S213/S217 as a mechanosensitive switch that is both necessary and sufficient for the fibroblast-to-myofibroblast transition. They validated these predictions in an independent transcriptomic dataset from patients with idiopathic pulmonary fibrosis, showing that NFATC4 expression increased with disease severity. Prior work has implicated NFATC4 activation in cardiac and hepatic fibrosis, suggesting that this single modification may serve as a convergence point for mechanical and cytokine signals across fibrotic diseases.